Anatomic Evaluation of Percutaneous Achilles Tendon Lengthening. (April 2018) - Phillips, Sierra; Shah, Ashish; Staggers, Jackson Rucker; Pinto, Martim; Godoy-Santos, Alexandre Leme; Naranje, Sameer; de Cesar Netto, Cesar
Background: The objective of the study was to evaluate the accuracy of percutaneous Achilles tendon lengthening (TAL) using a triple hemisection technique and the improvement in ankle dorsiflexion. Methods: Ten fresh-frozen above-knee cadaveric specimens were used. A percutaneous triple hemisection of the Achilles tendon (proximal, intermediate, and distal) was performed. Maximum ankle dorsiflexion was evaluated pre- and postprocedure with a digital goniometer. After proper dissection, the relative width of the cuts was noted. Following forced ankle dorsiflexion, displacement in the tensile gaps was measured in all 3 cuts with a precision digital caliper. Results: The overall relative width of the percutaneous cut was 51.3% ± 16.3% of the Achilles tendon diameter, 44.3% ± 13.6% for the proximal cut, 50.3% ± 15.6% for the intermediate cut, and 59.3% ± 18.4% for the distal cut. Tendon excursion averaged 13.0 ± 3.8 mm for the proximal cuts, 12.5 ± 4.7 mm for the intermediate cuts, and 8.2 ± 3.7 mm for the distal cuts. One cadaver had a complete rupture of the Achilles tendon and was excluded from the excursion data analysis. The mean range of motion for ankle dorsiflexion was 8.1 ± 3.9 degrees preprocedure and 27.6 ± 5.3 degrees postprocedure. The dorsiflexion angle significantly increased ( P < .0001) at an average of 19.5 ± 5.0 degrees following TAL. Conclusion: Our cadaveric study demonstrated that the percutaneous triple hemisection of the Achilles was an accurate technique that provided successful lengthening of the tendon and increased ankle dorsiflexion. Complete ruptures are possible complications. Clinical Relevance: Our cadaveric study showed that in a clinical situation, triple hemisections of the Achilles tendon can be performed reliably, with significant improvement of the ankle dorsiflexion, mainly through increased tendon excursion at the proximal and intermediate cuts, and with low risk of complete ruptures.